Why pay for free play? Investigating the excessive in-game purchases made by mobile legends gamers in the Philippines - Samonte, Piolo Louise Austria (Animo Repository, 2023)
With a valuation of $274 billion, the mobile gaming market is experiencing remarkable growth, becoming one of the most lucrative sectors in the electronic gaming industry. It is thus vital to investigate the correlation between Purchase Intentions and Actual Purchases among Philippine players of Mobile Legends: Bang Bang, a prevalent mobile multiplayer online battle arena (MOBA) game. The study also explores the impact of Impulsive Buying Tendency, Eudaimonic Gaming Experience, and Microtransaction Type on this relationship. Drawing from a diverse sample of 497 participants aged 18 to 45, sourced from De La Salle University Campus and Mobile Legends-related Facebook groups, the researchers deployed Jamovi and SPSS software for data analysis. Techniques employed included descriptive statistics, correlation analysis, and regression modeling. The findings indicate that, when considered collectively, the moderating variables exert a significant influence on players' actual in-game item purchases through various microtransactions in Mobile Legends: Bang Bang. However, the individual impact of these moderators on purchasing behavior was not found to be substantial. By shedding light on the purchasing behavior of Mobile Legends players, this study offers valuable insights for game developers, enabling them to better cater to their audience and optimize revenue generation.